Perspective of Family Members of Transitions to Alternative Levels of Care in Anglo-Saxon Countries. (21st February 2018) - Merla, C.; Wickson-Griffiths, A.; Kaasalainen, S.; Dal Bello-Haas, V.; Banfield, L.; Hadjistavropoulos, T.; Di Sante, E.
Abstract : This scoping review explores circumstances surrounding the decision about, and eventual experience of, transitioning older adults into alternative levels of housing (ALH), such as long-term care. This topic is examined from a family member perspective, given their exposure and involvement in the care of older adult relatives during this transitional period. The scoping review methodology is based on the framework of Arksey and O'Malley and subsequent recommendations from Levac, Colquhoun, and O'Brien. Approximately 470 articles were reviewed covering the period between 2000 and November 2014; 37 articles met inclusion criteria. A temporal organization of themes was used to describe the experiences of family members in the pretransition, active transition, and posttransition periods of moving older adult relatives into ALH. This paper highlights the transitional period as a time of crisis, with a lack of planning, support, and transparent discussion. This study identifies a need for future research on the potential benefits of family support groups, interim transitional housing options, different models of ALH, changing roles in the posttransition period, and the need for a comprehensive list of housing options for older adults. Results have the potential to inform policy/practice and improve the lives of older adults and their family.